Low Doses of Tetracycline Trigger the E. coli Growth: A Case of Hormetic Response. Issue 4 (1st October 2013) - Migliore, Luciana; Rotini, Alice; Thaller, Maria Cristina
Hormesis is a biphasic dose-response relationship, occurring when low concentrations of toxic agents elicit apparent improvements. In this work, the ability of sub-inhibitory concentrations of Tetracycline to induce hormetic response in a model organism was investigated. To this aim a reference strain of Escherichia coli, MG1655, was exposed to six decreasing doses of Tetracycline (between 0.12 and 0.00375 μg/ml), much lower than the Minimal Inhibitory Concentration (4 μg/ml). An hormetic increase was observed at the intermediate concentrations (0.015–0.03 μg/ml) of the tested range. The Colony Forming Unit number, indeed, rose up to 141% and 121% as compared to the control. At the highest (0.12 μg/ml) and lowest (0.00375 μg/ml) concentrations a slight decrease in CFU number was found. Results demonstrated that, in Escherichia coli, low concentrations of Tetracycline bias the bacterial numerical increase through a hormetic response; the dose-response curve describing this numerical increase is an U-inverted curve. Furthermore, these data confirm that hormesis is common to many - if not all - living systems, including bacteria; they underline the relevance of a deepened knowledge of both the effects and the possible consequences of exposure to low doses of contaminants.